Application of botanical pesticides in organic agriculture production: Potential and challenges - Toan, Dao Huy; Hoang, Dao Van; Hoang, Vu Dinh; Quang, Le Dang; Lam, Tran Dai (Vietnam Journal of Science and Technology, 2021)
In the context of agricultural pest management, botanical pesticides are best suited for use in organic food (agricultural) production, due to their safety to humans and the environment compared to conventional pesticides. Compounds of plant origin can be highly effective, with diverse and multiple mechanisms of action, while having low toxicity towards non-target organisms. However, the large-scale application of these products for pest control is limited by their poor stability and other technological issues. An overview of botanical pesticides is presented in this paper. Trends and challenges in the research and application of botanical pesticides in Vietnam are also discussed.